Observational study on postoperative JAK inhibitor and corticosteroid therapy following non-cultured epidermal cell suspension transplantation in stable vitiligo patients - Yixuan Zhang; Yingying Xu; Wenjun Cui; Xueli Ding; Yuyang Gu; Xuejun Zhang; Min Li (Journal of Dermatological Treatment)
Objective To compare the efficacy and safety of oral corticosteroids and JAK inhibitors as adjunctive treatments following non-cultured epidermal cell suspension (NCES) transplantation in patients with stable vitiligo.Methods Data were collected from 12 patients with stable vitiligo who underwent NCES transplantation at the Fourth Affiliated Hospital of Soochow University between June 2023 and December 2024. Postoperatively, 36 lesions (from 7 patients) were treated with oral corticosteroids, and 34 lesions (from 5 patients) with upadacitinib, totaling 70 vitiligo lesions evaluated. Clinical efficacy and safety were assessed over a 6-month follow-up period.Results Both treatment groups showed similar mean repigmentation rates at 6 months. However, the distribution of responses differed. Patients treated postoperatively with JAK inhibitors demonstrated a more polarized pattern, while those receiving corticosteroids showed a more uniform distribution. Anatomical analysis revealed significantly better responses in the face and trunk compared to acral areas in both groups. Notably, JAK inhibitors showed potential advantages in traditional treatment-resistant regions such as the limbs. No serious adverse events were observed in either group.Conclusion Both JAK inhibitors and corticosteroids appear to be safe and effective postoperative options following NCES. The choice of immunomodulatory strategy may influence repigmentation patterns, especially at different anatomical sites.